Implementing Self-Paced Learning Method To Increase Critical Thinking Skills And Mathematics Concept Mastery Of Grade 1 Students In XYZ School - Juniarsih Sinaga; Yeppy Sihotang (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2023)
Education is an important factor in the formation of a new, superior generation. Education is dynamic because every generation is different and the situations they face also change. In classroom learning, teachers often find problems in the concept mastery, interest, and critical thinking skill of grade 1 students, especially in Mathematics. In this journal, the researcher discusses the implications of implementing self-paced learning using activity centers in grade 1. This journal was made using the literature research method and class experiment. Class experiments that are carried out include central activities that are presented in various activities that accommodate various student learning styles. The researcher found that implementing self-paced learning in Mathematics for grade 1 students through activity centers could increase students' motivation, interest, concept mastery and critical thinking skill in completing their Mathematics lesson in classroom. The final result of this study is that it can improve students' critical thinking skills and concepts mastery abilities by applying the self-paced learning method in the classroom for grade 1 students.